Advances in the study of the conduction modes in SnO2 varistors - Parra, Rodrigo (2007)
The microstructure and electrical properties of the SnO2Co3O4Nb2O5La2O3 varistor system prepared through the conventional mixed oxides route were characterised. The electrical breakdown field (Er) and the non-linear coefficient (α) were determined from current density versus electric field curves. The barrier height and the concentration of donors were calculated by fitting the experimental data from impedance spectroscopy measurements assuming the formation of Schottky barriers at the grain boundaries and electrical conduction to occur due to tunnelling and thermionic emission. A model that takes into account the tunnelling contribution yielded more accurate results than a model based only on thermionic emission.